Implementation of Chucking Handling Towards The Ability of Mother In Helping Children at Adzikri Merakurak Paud, Tuban District - Ryandini, Tiara Putri; Pitaloka, Dyah; Faqih, Moh Ubaidillah (Jurnal Midpro, 2021)
The choking of toodlers was caused by a foreign body that entered the mouth. Giving chokes help needed a choking handling training to improve mother's ability in addressing choke cases. This research aims to determine implementation of chucking handling towards the ability of mother in helping children at Adzikri Merakurak Paud, Tuban District. This research uses the experimental analysis method with the One-group Pre-Post Test Design approach. Sampling techniques using the probability sampling technique (Simple random Sampling). The number of samples in this study was 25 respondents. The instrument used is a questionnaire about maternal abilities. This research uses the Wilcoxon Sign Rank Test with the level of the significance of α = 0.05 and the calculation using the SPSS software application is obtained by the value p = 0.000 where 0.000 <0.05, the H1 is accepted. The results of the analysis showed that most of the maternal ability before the training was choked handling has enough ability and after the training was given chokes handling almost all mothers have good ability. The concluded that there is the influence of choking handling training on Mother's ability in child relief in the PAUD Adzikri Merakurak. From the results of the study can be concluded that the training of choke treatment can improve mother's ability in children's relief